Low temperatures are required to induce the development of fertile flowers in transgenic male and female early flowering poplar (Populus tremula L.) - Hoenicka, Hans (2016)
Until now, artificial early flowering poplar systems have mostly led to the development of sterile flowers. In this study, several strategies aimed at inducting fertile flowers in pHSP::AtFT transgenic poplar were evaluated, in particular the influence of temperature and photoperiod. Our results provide evidence that temperature, and not photoperiod, is the key factor required for the development of fertile flowers in early flowering poplar. Fertile flowers were only obtained when a cold treatment phase of several weeks was used after the heat treatment phase. Heat treatments induced AtFT gene activity through activation of the heat-shock promoter (pHSP). Photoperiod did not show a similar influence on flower fertility as pollen grains were obtained under both long- and short-day conditions. Fertility was confirmed in flowers of both male and female plants. For the first time, crosses were successfully performed with transgenic female early flowering poplar. All mature flowers obtained after 8 weeks of inductive treatments were fertile. Gene expression studies also confirmed that cold temperatures influenced expression of poplar genes homologous to 'pollen development genes' from Arabidopsis thaliana (L.) Heynh. Homology and expression patterns suggested a role for PtTDF1, PtBAM1, PtSERK1/2 and PtMS1 on anther and pollen development in poplar flowers. The system developed in this study allows a fast and very reliable induction of fertile poplar flowers in a very short period of time. The non-reproductive phase, usually 7-10 years, can now be shortened to 6-10 months, and fertile flowers can be obtained independently of the season. This system is a reliable tool for breeding purposes (high-speed breeding technology), genomics and biosafety research.